Information asymmetry in voluntary environmental agreements: theory and evidence from UK climate change agreements. (13th January 2020) - Adetutu, Morakinyo O; Stathopoulou, Eleni
Abstract: Voluntary environmental agreements (VEAs) are often plagued by adverse selection problems, because the regulator has imperfect information about firm-specific production technologies and abatement costs. We explore this issue using the UK climate change agreement (CCA) as a case study. First, we present a theoretical emulation of the programme. Second, we resolve the regulator's asymmetric information problem by estimating unobserved energy efficiency (EE) using production theory. Third, we use microdata from three confidential manufacturing surveys to empirically test how limited information impacts resource allocation within the scheme. In line with the problem of limited information about firm production technologies, we find that firms with lower levels of EE receive higher CCA tax discounts. This finding holds over a range of robustness tests.